Wandering spleen with torsion of splenic vein and gastric varicies - Manzoor Aaqib; Shah Omair; Choh Naseer; Shera Tahleel; Bhat Ovais; Shera Faiz; Shah Mubashir (Elsevier, 2021)
Wandering spleen is a rare entity and can be a great imitator. Varied presentations have been described. We a present a case, the first in our center, with pelvic spleen associated with splenic vein torsion and secondary gastric varices. Presentation of our patient was with haematemesis which settled after splenectomy.